Dans ce camp a été inauguré un "Coin Blanc" parrainé par une comité Anglo-Américain. Serie de 3 photos
Dans ce camp a été inauguré un "Coin Blanc" parrainé par une comité Anglo-Américain. Serie de 3 photos.